Tree allometry and crown shape of four tree species in Atlantic rain forest, south-east Brazil - Alves, Luciana F.; Santos, Flavio A. M. (Journal of tropical ecology, 2002)
The allometry of crown shape and trunk diameter with tree height were analysed for four tree species in a tropical lowland rain forest, southeast Brazil. The dimensional relationships of a subcanopy species (Garcinia gardneriana) were contrasted with those of two canopy (Chrysophyllum flexuosum and Swartzia simplex) and one emergent species (Sloanea guianensis). For all trees ≥ 1 cm dbh, we recorded dbh, total height, branching height, crown area, crown width and crown length. Observed allometric relationships indicated interspecific variation in trunk diameter and crown shape with height. All species conformed to the elastic similarity model, except the emergent one that showed thicker trunks and a scaling exponent conforming to the constant stress model. The general allometric function used to describe the overall relationship (all sizes combined) did not specify exceptional variation in crown shape between species of contrasting adult stature (emergent vs. subcanopy species). However, when allometric relationships through ontogeny were considered, different strategies of growth, maintenance and expansion of crown became evident. Crown shapes were much more variable in canopy and emergent species than in the subcanopy one, suggesting that larger-statured species might be more flexible in the relative allocation of energy to height, diameter, and crown growth than smaller-statured ones. Notwithstanding, it is suggested that it is not possible adequately to predict allometric relationships only by adult stature/canopy position. Allometric variation may be also related to size-dependent changes in demographic traits and/or different responses to light availability among tree species.